Training on Interactive Extension Media Development (PADI HEBAT) to Enhance Agricultural Extension Officers' Skills in Supporting Food Security - Jarlis, Roni; Amelia, Kiki; Supriyanti, Juli; Hendrita, Vivi; Syuhada, Fildza Arief; Alatas, Andi; Fevria, Resti; Putri, Santi Diana; Putra, Ahadul (Pelita Eksakta, 2025)
Sijunjung Regency has significant potential for rice farming development, supported by 1,643 farmer groups spread across 8 sub-districts and 80 agricultural extension officers. However, extension effectiveness is often hindered by limited attractive and interactive media. Data shows that 90% of 80 extension officers lack skills in developing effective extension media, with only 40% of farmers benefiting from interactive media. This community service program aimed to provide training on creating interactive media (brochures and pamphlets) for PADI HEBAT (Superior, Effective, ADDIE-based, and Measurable Rice) using Canva platform. The Research and Development (R&D) approach was employed with comprehensive training covering material socialization, hands-on practice, technology implementation, mentoring, and program sustainability. Results showed significant improvements: knowledge index increased from 71.19% to 78.66%, complete skills transformation from zero to competent level, motivation enhancement with 73.5% participants achieving high category, and successful implementation of digital media in routine extension activities. The program successfully transformed extension officers into digitally-literate professionals capable of creating attractive interactive extension materials